Shuhe granule for insomnia: study protocol for a double-blind, randomized, placebo-controlled trial - Gao, Yu; Chen, Xiangbin; Li, Yuxi; Shen, Yuchuan; Chen, Xinyi; Xu, Qing; Peng, Mengling; Xu, Wen; Yuan, Jiamin; Hu, Yuanyuan; Chen, Xiankun; Xu, Biyun; et al. (Frontiers in Pharmacology, 2025)
IntroductionModern medical treatment of insomnia is often associated with issues like addiction, drug resistance, and a high risk of relapse post drug withdrawal. To tackle these challenges, the Chinese medicine formula Shuhe granule (SHG) has been employed in insomnia treatment at Guangdong Provincial Hospital of Chinese Medicine. Despite this, there is currently a lack of reliable evidence from evidence-based trials to support the widespread use of SHG in insomnia treatment. Therefore, we have developed a randomized controlled trial to assess the efficacy and safety of SHG in insomnia treatment.MethodThis study will be a single-center, double-blind, randomized, parallel group, placebo-controlled clinical trial involving a total of 160 eligible patients aged between 18 and 65. Participants will be randomly assigned to either the intervention group, receiving SHG, or the placebo group receiving placebo granules. Follow-up visits will occur every 2 weeks from baseline to 2 months. The primary outcome is the perceived insomnia severity measured by the Insomnia Severity Index. The secondary outcome measures include the Pittsburgh Sleep Quality Index, Fatigue Severity Scale, Patient Health Questionnaire, Generalized Anxiety Disorder, Visual Fatigue Analogue Scale, Traditional Chinese medicine syndrome score, and Polysomnography.DiscussionThe results of the study are expected to provide evidence of high methodological and reporting quality on the efficacy and safety of SHG for insomnia.Trial Registration Numbershttp://itmctr.ccebtcm.org.cn/, ITMCTR2024000035.